2020
DOI: 10.1055/s-0040-1701226
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Sedative Antihistamines and the Duration of Febrile Seizures

Abstract: Some studies have shown that sedative antihistamines prolong febrile seizure duration. Although the collective evidence is still mixed, the Japanese Society of Child Neurology released guidelines in 2015 that contraindicated the use of sedative antihistamines in patients with febrile seizure. Focused on addressing limitations of previous studies, we conducted a cross-sectional study to evaluate the relationship between febrile seizure duration and the use of sedative antihistamines. Data were collected from pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Após a análise dos dados, observou-se que no grupo dos anti-histamínicos sedativos (AHS) uma proporção maior de pacientes com crises convulsivas superiores a 5 minutos foi predominante, contudo, não houve diferença significativa entre os grupos, ou seja, de acordo com (Daida et al; e de 13 a 18 anos (14,7%), intubação em crianças maiores de 12 anos (7,78%) e adultos (9,71%) e disritmia ventricular, que acometeu 3 crianças menores de 18 anos.…”
Section: Discussionunclassified
“…Após a análise dos dados, observou-se que no grupo dos anti-histamínicos sedativos (AHS) uma proporção maior de pacientes com crises convulsivas superiores a 5 minutos foi predominante, contudo, não houve diferença significativa entre os grupos, ou seja, de acordo com (Daida et al; e de 13 a 18 anos (14,7%), intubação em crianças maiores de 12 anos (7,78%) e adultos (9,71%) e disritmia ventricular, que acometeu 3 crianças menores de 18 anos.…”
Section: Discussionunclassified
“…While the new-generation H 1 A has fewer side effects due to not passing the blood-brain barrier, it should be used with caution in younger children since this agent may disrupt the central anticonvulsant histaminergic system (21). Some studies have supported the use of optimal doses of H 1 antagonists in feverish children with allergic symptoms (13,18,24). Nevertheless, Daida et al (13) reported no significant association between antihistamine use and seizure duration, recommending the use of antihistamines for patients with a history of FS.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have supported the use of optimal doses of H 1 antagonists in feverish children with allergic symptoms (13,18,24). Nevertheless, Daida et al (13) reported no significant association between antihistamine use and seizure duration, recommending the use of antihistamines for patients with a history of FS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation